Abiotic dechlorination in rock matrices impacted by long-term exposure to TCE. (January 2015) - Schaefer, Charles E.; Towne, Rachael M.; Lippincott, David R.; Lacombe, Pierre J.; Bishop, Michael E.; Dong, Hailiang
Highlights: TCE abiotic dechlorination reactions were measured in rock matrices. Abiotic dechlorination of TCE occurred in rock matrices exposed to TCE for decades. Reaction rate constants were similar to those observed in rock not exposed to TCE. Abiotic reactions are expected to have an impact on TCE transport in rock matrices. Abstract: Field and laboratory tests were performed to evaluate the abiotic reaction of trichloroethene (TCE) in sedimentary rock matrices. Hydraulically conductive fractures, and the rock directly adjacent to the hydraulically conductive fractures, within a historically contaminated TCE bedrock aquifer were used as the basis for this study. These results were compared to previous work using rock that had not been exposed to TCE (Schaefer et al., 2013) to assess the impact of long-term TCE exposure on the abiotic dechlorination reaction, as the longevity of these reactions after long-term exposure to TCE was hitherto unknown. Results showed that potential abiotic TCE degradation products, including ethane, ethene, and acetylene, were present in the conductive fractures. Using minimally disturbed slices of rock core at and near the fracture faces, laboratory testing on the rocks confirmed that abiotic dechlorination reactions between the rock matrix and TCE were occurring. Abiotic daughter products measured in the laboratory under controlled conditions were consistent with those measured in the conductive fractures, except that propane also was observed as a daughter product. TCE degradation measured in the laboratory was well described by a first order rate constant through the 118-d study. Observed bulk first-order TCE degradation rate constants within the rock matrix were 1.3 × 10 −8 s −1 . These results clearly show that abiotic dechlorination of TCE is occurring within the rock matrix, despite decades of exposure to TCE. Furthermore, these observed rates of TCE dechlorination are expected to have a substantial impact on TCE migration and uptake/release from rock matrices.